Vetiver Grass for the Remediation of Soil Contaminated with Heavy Metals - Roongtanakiat, Nualchavee; Chairoj, Prapai (Agriculture and Natural Resources, 2001)
Three vetiver grass ecotypes, Kamphaeng Phet, Ratchaburi and Surat Thani were planted in soil supplemented with different amounts of manganese (Mn), zinc (Zn), copper (Cu), cadmium (Cd) and lead (Pb). It was found that these heavy metals did not affect the growth of the vetiver grass, even though the uptake amount increased as the applied amount increased. Ratchaburi ecotype gave the highest shoot dry weight and lowest root weight and at the same time had significantly higher Mn, Zn and Cd amounts in shoots than Surat Thani and Kamphaeng Phet ecotypes. However, Ratchaburi and Kamphaeng Phet ecotypes showed similar copper uptake. The root of Ratchaburi ecotype could also absorb significantly higher amounts of Zn, Cd and Pb than those of Surat Thani and Kamphaeng Phet ecotypes. For Mn and Cu, Ratchaburi and Surat Thani ecotypes could uptake more than those of Kamphaeng Phet. As expected, the residual heavy metal in soil increased as the applied amount increased. The soil planted with Ratchaburi vetiver ecotype had less residual heavy metals than that planted with the other two ecotypes since it absorbed more heavy metals. Therefore, this specific ecotype would be useful for remedying soil contaminated with heavy metals.